«ҚЫРЫҚ ҚЫЗ» ДӘСТАНЫ ҲӘМ ОНЫҢ ЖЫРАЎЛАР РЕПЕРТУАРЫНДАҒЫ ӨЗГЕШЕЛИГИ - Зарипова, Зулфия Сарсенбаевна (ILIM hám JÁMIYET, 2026)
The article discusses the epic poem "Qiriq qiz" which is part of the oral tradition of the Karakalpak people. The recording of the dastan, its periods of origin, performers, compositional structure, and scientific and practical works on this topic are presented.